Unscrambling the Friendship Code: A Psychoanalytic Exploration of the Bollywood Film: “Dor” - Vishal K R (International Journal of Indian Psychȯlogy, 2022)
Dor is a hindi movie released in 2006 directed by Nagesh Kukunoor. It tells the story of two women from different backgrounds whose lives become intertwined when one seeks justice for her husband’s death, and the other helps her navigate through the legal system to prevent her husband’s execution. The film explores themes of friendship, resilience, and the power of determination. From this film, we aim to provide an in-depth psychoanalysis of the movie theme and the characters using Freud’s theory of psychoanalysis.